(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2014)
Caryocar brasiliense, popularly known in Brazil as “pequi”, is a species widely distributed in the Brazilian Cerrado. The seeds are surrounded by a woody endocarp coated with a yellow fleshy mesocarp rich in oil and vitamin A, whose oil has a useful role in the treatment of skin aging and protection of human skin against UV-induced damage and skin hydration. The aim of this study was to evaluate the effect of cosmetic formulations containing pequi oil (Caryocar brasiliense) on skin hydration, after a single application. Hydration effect assessment was performed by applying the formulations under study (Control – no formulation, vehicle, and vehicle + pequi oil) onto forearm skin of 30 human volunteers. Skin capacitance and Transepidermal Water Loss (TEWL) measurements were analyzed before, and at 1, 2 and 3 hours after, a single application. Evaluation results of a single application of the vehicle containing pequi oil showed an increase in stratum corneum water content, indicating a skin moisturizing effect. Results of the evaluation of immediate effects of TEWL demonstrated that the vehicle containing pequi oil significantly increased skin moisture during the 3 h evaluation period. The formulations containing pequi oil showed clinical efficacy, increasing stratum corneum water content and enhancing skin barrier function.